Serotonin 5-HT1 Receptors Potentiate Histamine and Thrombin Stimulated Prostaglandin Synthesis in Endothelial Cells - Kilbourne, Edward J.; Winneker, Richard C. (Thrombosis and Haemostasis, 2001)
The ability of serotonin 5-HT1 receptors to increase vascular tone was previously found to be activated by vasoconstrictiors such as hista-mine. In this study, treatment of cultured human aortic endothelial cells (HAEC) with the 5-HT1-selective agonist 5-carboxamidotryptamine (5-CT) alone had no effect on the levels of prostaglandin F2α (PGF2α) or 6-keto-prostaglandin F1α (6-keto PGFα1). However, 5-CT potentiated the histamine and thrombin stimulated increases in prostaglandins released by HAEC. In the presence of histamine, increasing doses of 5-CT caused a steep rise in PGF2α levels resulting in an increase in the ratio of PGF2α over 6-keto PGF1α . The ability of 5-CT to potentiate prostaglandin production was correlated with its ability to potentiate the histamine and thrombin mediated mobilization of arachidonic acid. These results demonstrate that the ability of 5-HT1 receptors to stimulate prostaglandin production in endothelial cells is activated by histamine and thrombin.
Keywords: Endothelial cells; serotonin; histamine; prostaglandin